Borehole Equilibration: Testing a New Method to Monitor the Isotopic Composition of Tree Xylem Water in situ - Marshall, John D.; Cuntz, Matthias; Beyer, Matthias; Dubbert, Maren; Kuehnhammer, Kathrin (Frontiers in Plant Science, 2020)
Forest water use has been difficult to quantify. One promising approach is to measure the isotopic composition of plant water, e.g. the transpired water vapor or xylem water. Because different water sources, e.g. groundwater versus shallow soil water, often show different isotopic signatures, isotopes can be used to investigate the depths from which plants take up their water and how this changes over time. Traditionally such measurements have relied on the extraction of wood samples, which provide limited time resolution at great expense, and risk possible artefacts. Utilizing a borehole drilled through a tree’s stem, we propose a new method based on the notion that water vapor in a slow-moving airstream approaches isotopic equilibration with the much greater mass of liquid water in the xylem. We present two empirical data sets showing that the method can work in practice. We then present a theoretical model estimating equilibration times and exploring the limits at which the approach will fail. Given long enough boreholes and slow enough flow rates, tThe method provides a simple, cheap, and accurate means of continuously estimating the isotopic composition of the source water for transpiration.